The potency of finding a new antimalarial drug from Indonesian sea - Murtihapsari Murtihapsari; Ekowati Chasanah (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2010)
Malaria is deadly disease killing 1.5-3 million peoples on the globe a year. In Indonesiaespecially Papua, malaria is a number one killer disease. Finding resources of new drug malariais seriously needed due to resistance to many Chloroquin by Plasmodium. About 65% of marinePorifera from 12 classes in the taxa have recently contributed to our knowledge of biomedicalmaterial. Sponges are abundantely inhabiting Indonesian waters. In recent discovery reportedthat marine sponge Xestospongiafrom Papua has possessed a great ability against Plasmodiumfalciparum.These evidence thus stated Indonesian water is home of the potential marine drug formalaria. For sustainable reason, production live specimen throughout sea culture should to behighlighted. This review presents a development of malaria disease and the potential of Indonesianmarine biota as biomedical material especially for malaria disease.